2013
DOI: 10.1002/marc.201200742
|View full text |Cite
|
Sign up to set email alerts
|

Star‐Shaped Polymer Consisting of a Porphyrin Core and Poly(L‐lysine) Dendron Arms: Synthesis, Drug Delivery, and In Vitro Chemo/Photodynamic Therapy

Abstract: A novel star-shaped polymer, porphyrin-poly(L-lysine) dendrons (PP-PLLD), is synthesized by the click reaction between azido-modified porphyrin and propargyl focal point poly(L-lysine) dendrons. Its chemical structure is characterized by (1) H nuclear magnetic resonance, Fourier transform infrared spectroscopy, and gel permeation chromatography (GPC) is analyses etc. Due to its amphiphilic property, the obtained PP-PLLD has a low critical micelle concentration in an aqueous solution, and can load doxorubicin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 34 publications
0
49
0
1
Order By: Relevance
“…What was more, the antibacterial activity of Cu-Nd@ZrP1 was higher than those of Cu@ZrP and Nd@ZrP, so the Cu-Nd@ZrP1 showed the great potential application as an antibacterial powder. Compared with other reports [41][42][43][44], we concluded that Cu-Nd@ZrP was a relatively biocompatible nanomaterial with slight cytotoxicity.…”
Section: Cytotoxicity Testmentioning
confidence: 56%
“…What was more, the antibacterial activity of Cu-Nd@ZrP1 was higher than those of Cu@ZrP and Nd@ZrP, so the Cu-Nd@ZrP1 showed the great potential application as an antibacterial powder. Compared with other reports [41][42][43][44], we concluded that Cu-Nd@ZrP was a relatively biocompatible nanomaterial with slight cytotoxicity.…”
Section: Cytotoxicity Testmentioning
confidence: 56%
“…Also, no quantitative analysis of the in vitro cytotoxicity, for example the IC 50 of the DOX-loaded micelles with and without photodynamic treatment, was investigated. Moreover, no in vivo performance was assessed [53]. Thus, it is necessary to develop and identify novel photodynamic nanoparticles for anti-cancer drug delivery and synergy therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity difference was bigger at 6 h than that at 2 h, implying both time and micellarization of Zn-Por had effect on the cell uptake. Furthermore, the red fluorescence of Zn-Por looked as coming from both the nucleus and cytoplasm areas in the SNG-treated cells at 2 h, and mainly from the nuclei at 6 h, while mainly from the cytoplasm area in the free Zn-Por-treated cells at both 2 and 6 h. This is because Zn-Por has limited solubility in cell culture medium and its entry into cells depends on its molecular diffusion through the cell membranes, whereas SNG particles diffuse through the cell membranes and enter the cells efficiently by an active mechanism [38]. The red fluorescence from the nucleus area means that the SNG as a whole or its dissociation products have good affinity to the nuclear membrane and can enter the nuclei with ease.…”
Section: Intracellular Endocytosismentioning
confidence: 91%